miR-185 Inhibits Fibrogenic Activation of Hepatic Stellate Cells and Prevents Liver Fibrosis - Li Zhou; Shunai Liu; Ming Han; Yanhua Ma; Shenghu Feng; Jing Zhao; Hongping Lu; Xiaoxue Yuan; Jun Cheng (Elsevier, 2018)
Recent studies have shown the effect of microRNAs on HSC activation and transformation, which is essential for the pathogenesis of liver fibrosis. In our study, we explored the role of miR-185 in liver fibrosis. Plasma miR-185 was detected in hepatitis B virus-related liver fibrosis patients (S2/3, n = 10) by Illumina HiSeq sequencing, and healthy volunteers were selected (n = 8) as the control group. We found that the plasma miR-185 level in fibrosis patients was significantly downregulated. CCl4-induced fibrosis tissues in mouse livers and TGF-β1-activated HSCs also presented downregulated miR-185 concomitant with an increased expression of RHEB and RICTOR. To explore the correlations, LX-2 cells were transiently transfected with miR-185 mimics. The expression levels of α-SMA, collagen I, and collagen III were decreased as well as RHEB and RICTOR. Inhibition of endogenous miR-185 increased fibrogenic activity. Furthermore, dual-luciferase reporter assays indicated that miR-185 inhibited the expression of RHEB and RICTOR by directly targeting their 3' UTRs. Moreover, silencing RHEB and RICTOR suppressed α-SMA and collagen expression levels. In conclusion, miR-185 prevents liver fibrogenesis by inhibiting HSC activation via inhibition of RHEB and RICTOR. These results provide new insights into the mechanisms behind the anti-fibrotic effect of miR-185.